Antitumor and anti‐metastatic mechanisms of Rhizoma paridis saponins in Lewis mice. Issue 2 (17th November 2017) - Man, Shuli; Chai, Hongyan; Cui, Jingxia; Yao, Jingwen; Ma, Long; Gao, Wenyuan
Abstract: Lung cancer is one of the most common causes of death in the world. Rhizoma paridis saponins (RPS) have been found to show inhibition of pulmonary adenoma in previous research. However, the detailed mechanisms of RPS from a holistic view have not been established. In this study, Lewis pulmonary adenoma mice were successfully established to analyze the pathways involved in RPS intervening tumor formation and progression. As a result, RPS inhibited levels of cytokines or receptors such as VEGFD, VEGFR3, RAGE, IL6R, IL17BR, and CXCL16 which were regarded as the initiators induced tumor cell proliferation, adhesion, angiogenesis, and invasion. Meanwhile, RPS raised the content of SOD and CAT enzymes and thereby inhibited the aberrantly active NF‐κB, and phosphorylation of PI3K/Akt and MAPK (including p38, Erk1/2, and JNK) signaling pathways. Soon after, RPS changed mRNA expression of nuclear factors containing NF‐κB, HIF‐1A, STAT3, and Jun, and consequentially suppressed the expression of angiogenesis, lymphangiogenesis, adhesion, inflammation, and invasion enzymes. In conclusion, this research provided a holistic view to understand the multi‐target antitumor mechanisms of RPS which promoted the application of RPS in the future.